Continental‐scale variation in seaweed host‐associated bacterial communities is a function of host condition, not geography. (4th August 2015) - Marzinelli, Ezequiel M.; Campbell, Alexandra H.; Zozaya Valdes, Enrique; Vergés, Adriana; Nielsen, Shaun; Wernberg, Thomas; de Bettignies, Thibaut; Bennett, Scott; Caporaso, J. Gregory; Thomas, Torsten; Steinberg, Peter D.
Summary Interactions between hosts and associated microbial communities can fundamentally shape the development and ecology of 'holobionts', from humans to marine habitat‐forming organisms such as seaweeds. In marine systems, planktonic microbial community structure is mainly driven by geography and related environmental factors, but the large‐scale drivers of host‐associated microbial communities are largely unknown. Using 16S‐rRNA gene sequencing, we characterized 260 seaweed‐associated bacterial and archaeal communities on the kelp Ecklonia radiata from three biogeographical provinces spanning 10° of latitude and 35° of longitude across the Australian continent. These phylogenetically and taxonomically diverse communities were more strongly and consistently associated with host condition than geographical location or environmental variables, and a 'core' microbial community characteristic of healthy kelps appears to be lost when hosts become stressed. Microbial communities on stressed individuals were more similar to each other among locations than those on healthy hosts. In contrast to biogeographical patterns of planktonic marine microbial communities, host traits emerge as critical determinants of associated microbial community structure of these holobionts, even at a continental scale.